Analysis Of Half Slab Floor Plates In Slab-On-Pile Structures For The IKN Toll Road Construction Project, Section 3A-2: Karangjoang - KKT Kariangau Balikpapan Segment - Cahya Ningrum; Anis Aulia; Wahyu Yusuf Rio (Nusantara Civil Engineering Journal, 2024)
This study was conducted with the aim of determining the effect of alluvial deposits on the shear strength of clay soils of the New Kampung Formation with direct shear strength tests and variations in alluvial sediment mixtures of 0%, 10%, 20%, 30%, 40%, 50%. Based on the results of the original soil laboratory test, the percentage of sieve pass number 200=54.34%, liquid limit=45.31%, plastic limit=25.72%, plasticity index=19.59%, moisture content=28.64%, volume weight=3.52 grams/cm3, specific gravity=2.50, and in the USCS system entered the low plasticity clay group. Based on the results of laboratory tests of alluvial deposits, the percentage of passing the filter number 4=95.70%, passing the filter number 200=1.84%, moisture content=28.87%, and in the USCS system entered the poorly graded sand group. In the addition of alluvial sediment variations, there was a decrease in cohesion, namely, 0%=2.7452 kg/cm2, 10%=2.5380 kg/cm2, 20%=1.6575 kg/cm2, 30%=0.9841 kg/cm2, 40%=0.8460 kg/cm2, and 50%=0.5007 kg/cm2. In the addition of alluvial sediment variations, there was an increase in the depth of shear angle (∅) in the variation of 10% alluvial deposits and a decrease in variations of 20% to 50% alluvial deposits, 0%=32.182°, 10%=59.449°, 20%=56.319°, 30%=48.069°, 40%=45.469°, and 50%=39.451°.